JURIDICAL STUDY OF THE REGULATION OF CINEMATOGRAPHIC WORK VIEWING ON DIGITAL STREAMING PLATFORMS BASED ON THE INDONESIAN LEGAL SYSTEM - Dharliana Hardjowikarto; Dewi Kania; Eni Suhaeni; Ajeng Rahayu (Cirebon International Conference on Education and Economics Proceeding, 2024)
The viewing of cinematographic works on digital streaming platforms has become a significant phenomenon in the modern entertainment industry. Along with the ease of access, it also raises various legal issues, especially related to censorship and content control, and legal enforcement of censorship regulations and limitations in censorship of cinematographic works on digital streaming platforms has become a hot topic of discussion. This research aims to analyse the law enforcement of censorship regulations on cinematographic works and the factors that influence the limitations in censoring cinematographic works on digital streaming platforms. This research uses a normative juridical method by conducting a qualitative approach and analysing laws and regulations and opinions of legal experts. This research found that there are complexities and challenges in law enforcement against content censorship on digital streaming platforms, such as the lack of clarity of the parties entitled to censor cinematographic works on digital streaming platforms, and a vacuum in supervision of digital streaming platforms because the characteristics of digital streaming platforms are not fulfilled with the concept of broadcasting contained in broadcasting regulations.